Protecting broilers against Campylobacter infection by preventing direct contact between farm staff and broilers. (November 2016) - Battersby, Tara; Whyte, P.; Bolton, D.
Abstract: The objective of this study was to test the hypothesis that farm staff are the primary vector of Campylobacter transmission into broiler flocks. On 3 different farms and 5 different flocks (3 flocks on farm 1 and 1 flock on each of farms 2 and 3) a small section of the broiler house (3 × 2 m (farm 1) and 1 m × 1 m (farms 2 and 3)) was sectioned off using Perspex or plastic sheeting. This 'biosecure cube' (BC) was populated with 25–125 chicks (test birds), a small subset of the general population of up to 30, 000 (control) birds in the broiler house. The BC area incorporated the water and feed-lines thus the test and control birds had access to the same feed, water and air. However, unlike in the general broiler house, the farm staff had no direct access to this sub-population. Dead birds were aseptically removed by the researchers. The birds were tested for Campylobacter (faecal and/or caecal samples), on the day of chick arrival and every 7 days thereafter. In farm 1-flock 1 the general broiler population was Campylobacter -positive after 21 days but the test birds remained negative until day 35. The general broiler population in the other 4 flocks were Campylobacter positive as early as day 14, but in all cases the test birds remained negative. Moreover BC broilers were significantly ( P < 0.05) heavier than the control birds (400 g on average), at first thinning. It was therefore concluded that preventing direct contact between the farm staff and the broilers prevents Campylobacter infection in broilers. Highlights: Avoiding direct contact between staff and broilers prevents Campylobacter infection. Protected birds grew more rapidly than control broilers. Enhanced biosecurity would improve food safety, animal welfare and productivity.